Differential game of optimal pursuit for an infinite system of differential equations - Ibragimov, Gafurjan Ismailovich; Alias, Idham Arif; Waziri, Usman; Ja'afaru, Abbas Badakaya (Springer, 2019)
We study an optimal pursuit differential game problem in the Hilbert space l2r+1. The game is described by an infinite system of the first-order differential equations whose coefficients are negative. The control functions of players are subjected to integral constraints. If the state of the system coincides with the origin of the space l2r+1, then game is considered completed. We obtain an equation to find the optimal pursuit time. Moreover, we construct the optimal strategies for players.